Three new species of Mesovelia Mulsant & Rey (Hemiptera: Heteroptera: Mesoveliidae) from India - Jehamalar, E. Eyarin; Chandra, Kailash (Zootaxa, 2017)
Three new species of Mesovelia Mulsant & Rey, 1852 (Mesoveliidae: Mesoveliinae) are described from India. Mesovelia kumaria sp. nov. and Mesovelia lillyae sp. nov. are described from Kanyakumari District, Tamil Nadu and Mesovelia easaci sp. nov. is described from Meghalaya. Mesovelia easaci sp. nov. can be distinguished by the presence of a small gap between the median spinose tuft on the eighth abdominal sternum of the male, an inverted heart-shaped white mark on the membrane of the macropterous form and a flap-like posterolateral projection on the ninth abdominal segment of the female. Mesovelia kumaria sp. nov. can easily be identified by the absence of spines on the flexor region of the male fore femur and the presence of widely spaced and very small spinose setal tufts on the eighth abdominal sternum of the male. Mesovelia lillyae sp. nov. can be recognized by the absence of the spines on the basal half of the mid femur and the presence of a pair of brush-like spinal tufts in the centre of the eighth abdominal sternum in the males. Detailed illustrations of all three species described here are given.